Rancang Bangun Sistem Pembangkit Hybrid Dengan Tenaga Matahari Dan Tenaga Angin - Ahmad Akbar; Putrie Aurelia Riyono; Muhammad Arya Delwizar; Elkim Dwijayanto Malia; Indra Kelana; Nur Rani Alham (Politeknik Negeri Samarinda, 2020)
Electrical energy is one of the most important daily needs for humans. Electricity is used to power tools that are used daily, such as turning on the lights, TV, refrigerator, and others. Electrical energy can be generated easily, there are already many power plants that can create electricity from new and renewable energy such as solar power plants (PLTS) and wind power plants (PLTB). The two generators can be combined to form a new system, namely the Hybrid system. In this study design a hybrid system of solar thermal energy and wind energy. The system formed uses a power storage system that is with a battery. Then the energy from the battery can provide energy to the load. The average power generated from the PLTS design is 0.474 Watt and the average wind generator is 9.378 Watt. Then the average hybrid system produces a power of 0.551 Watt.